Forest and Land Fire Prevention Governance in Central Kalimantan: The Role of Government and Community - Alicia Dhela Setiani; Viona Okvelin Winey; Anita Apriyani; Witna Rudie S.M (Lembaga Pengembangan Kinerja Dosen, 2026)
Forest and land fires continue to be one of the most chronic environmental management problems in Central Kalimantan. This study will analyze how protection management is implemented, as well as how the roles of the government and community interact in preventing and managing forest and land fires. This study uses a qualitative approach with a literature review method. Several data researched by the authors show that forest fire management is shifting towards a collaborative approach involving various parties. However, implementation continues to face problems of institutional coordination, inconsistent local capacity, and low sustainability of community participation programs. Community-based prevention projects are effective in reducing fire risk, but require better institutional support and sustained government commitment. This study suggests that efficient fire protection governance depends on adaptive collaboration between government agencies and local communities, facilitated by clear coordination mechanisms and long-term environmental governance initiatives.